Right ventricular-pulmonary arterial coupling and pulmonary hypertension in hemodialysis: insights into structural cardiac changes and clinical implications - Buryskova Salajova, Kristina; Malik, Jan; Kaiserova, Lucie; Hladinova, Zuzana; Hruskova, Zdenka; Janakova, Simona; Tesar, Vladimir; Pesickova, Satu Sinikka; Michalickova, Kristyna; Rocinova, Katarina; Szonowska, Barbora; Valerianova, Anna (Renal failure, 2025)
OBJECTIVES: This cross-sectional analysis from the CZecking Heart Failure in patients with advanced Chronic Kidney Disease trial (ISRCTN18275480) examined pulmonary hypertension and right ventricular-pulmonary arterial coupling in patients on chronic hemodialysis. The aims of this analysis were: 1. To analyze relations between pulmonary hypertension and right ventricular-pulmonary arterial coupling with dialysis access flow and current hydration; 2. To analyze structural heart changes associated with right ventricular-pulmonary arterial uncoupling; 3. To reveal the prevalence, etiology and severity of pulmonary hypertension in the Czech hemodialysis population. METHODS: We performed expert echocardiography, vascular access flow measurements, bioimpedance analysis, and laboratory testing in 336 hemodialysis patients. RESULTS: Pulmonary hypertension was present in 34% (114/336) patients and right ventricular-pulmonary arterial uncoupling was present in 25% of patients with pulmonary hypertension. Only weak associations between the flow of the dialysis arteriovenous access and estimated pulmonary arterial systolic pressure and right ventricular-pulmonary arterial coupling was proved. There was a strong association between hydration status assessed by estimated central venous pressure with pulmonary arterial systolic pressure (Rho 0.6, p < 0.0001) and right ventricular-pulmonary arterial coupling (Rho -0.52, p < 0.0001) and association between overhydration to extracellular water ratio with pulmonary arterial systolic pressure (Rho 0.31, p = 0.0001) and right ventricular-pulmonary arterial coupling (Rho -0.29, p = 0.002). The prevalence of heart failure was significantly higher in patients with right ventricular-pulmonary arterial uncoupling (88% vs. 52%, p = 0.0003). CONCLUSION: These findings suggest that optimizing volume status and treating heart failure should be prioritized in hemodialysis patients to prevent pulmonary hypertension progression and right ventricular-pulmonary arterial uncoupling.
Keywords: senioři; Cross-Sectional Studies; Prevalence; arteria pulmonalis; Right ventricular-pulmonary arterial coupling; chronic hemodialysis; echokardiografie; Česká republika; Echocardiography; Hypertension, Pulmonary; Renal Dialysis; Middle Aged; mužské pohlaví; prevalence; průřezové studie; srdeční komory; Czech Republic; Pulmonary Artery; pulmonary hypertension; ženské pohlaví; plicní hypertenze; fluid overload; Humans; Heart Ventricles; lidé středního věku; dialýza ledvin; Kidney Failure, Chronic; chronické selhání ledvin; Female; Aged; arteriovenous access flow; heart failure; lidé; Male